LOCATION QUOTIENT ANALYSIS IN DETERMINING BASE AND NON-BASIC SECTORS IN EAST JAVA PROVINCE - Anwar, Chairil (Sekolah tinggi ilmu ekonomi pemuda, 2023)
One of the important factors in improving people's welfare is through the creation of an investment climate that is easy, fast and conducive. There are two positive impacts that can be enjoyed by the regions, when investment is growing fast and conducive. First, investment will be followed by other economic activities through the opening of new jobs so that people's income will automatically increase and will be followed by massive regional economic growth. Second, investment also provides opportunities for potential economic resources to be processed into renewable economic power in the real sector, which will ultimately lead to economic growth to increase people's welfare and reduce poverty. For this reason, it is necessary to identify the basic sectors and sub-sectors which are one of the stages in planning the expansion of strategic areas as centers of new economic growth. Therefore, Location Quotient Analysis is needed to determine the level of specialization of the economic sector in a particular area in utilizing its base sector or superior sector. The basic sector can be determined using the Location Quotient (LQ) method. The variable used to calculate the economic basis is the GRDP of an activity that is focused on activities within the local economic structure. Gross Domestic Product (GDP) is an important indicator to determine the economic condition of East Java Province in a certain period, both based on current prices and constant prices. The data collection process was carried out using a secondary data survey based on documents from the East Java Province and National BPS. from 2021 to 2022 per Quarter, the manufacturing sector, electricity and gas procurement, wholesale and retail trade, car and motorcycle repair, provision of food and drink accommodation, and the information and communication sector will be a stable basis in terms of increasing LQ scores and its GDP in a period of analysis. It is possible that these sectors have contributed to the increase in GRDP of East Java Province including all other sectors which are also the basis such as the Mining and Quarrying sector, the agricultural sector and others. Keywords: Sector Base, Location Quotient, GRDP, East Java Province